MENCIPTAKAN KEUNGGULAN BERSAING YANG BERKELANJUTAN MELALUI MANAJEMEN SUMBER DAYA MANUSIA - Harjanti, Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2004)
ABSTRACT Technology change, globalization, working force variety, working trend and business environment condition cause more competitive competition in business. Consequently organizations need to create competition excellence continuously in order to survive. The competition excellence can be created by changing the role and human resource management paradigm. The old paradigm placed human resource not in vital position, while new paradigm place it is as vital aspect in organization, so that human resource is considered to be crucial asset. Human resource management has to be able to manage human resource optimally in organization structure with strategic steps to improve human resource quality as human capital. It can be done by improving employee capability and employee commitment. Human resource is expected to have distinctive capabilities experience and know-how, since it has the ability to be organization distinction factor in competition by creating valuable, rare, uninitiated and uneasy substitute product, so continuous competition excellence is created. Keywords: competition excellence, human capital, employee capability, employee commitment. Â